Taxonomic status of Akodon oenos (Rodentia, Sigmodontinae), an obscure species from West Central Argentina - Pardiñas, Ulyses F. J.; Teta, Pablo; D’elía, Guillermo; Diaz, Gabriela B. (Zootaxa, 2011)
Akodon oenos Braun, Mares, and Ojeda, 2000 was described on a large sample of individuals collected from two localities near Mendoza city, Argentina. This sample was obtained in the 1980’s by Julio R. Contreras and María I. Rossi and labeled, but never published, as “Akodon minoprioi new species.” The description provided by Braun and collaborators was limited to craniodental and color pelage traits compared with those of five individuals of the sympatric form A. molinae Contreras, 1968. Akodon oenos was proposed as new and presumptively allied to the A. varius species group of Akodon. In February 2009 we collected an individual of Akodon in Llancanelo Natural Reserve, southern Mendoza, that morphologically fits the original description of A. oenos. Further study of some individuals of the type series of A. oenos reinforces this taxonomic hypothesis for the Llancanelo specimen. However, comparisons with other Akodon species overlooked by Braun and collaborators, reveals striking similarities with the widespread and phenotypically variable species A. spegazzinii Thomas, 1897. The evidence at hand, including morphological, karyological, and genetical traits, allows us to propose a new taxonomic scenario. A. oenos is considered here a junior synonym of A. spegazzinii and therefore belongs to the A. boliviensis species group of Akodon, extending the known geographic distribution for this species at least to southern Mendoza piedmont in the ecotone between the Monte and Patagonia eco-regions. More generally, this situation highlights the necessity when working with complex genera (as many sigmodontines are) to perform extensive comparisons and to use several sets of evidence in order to reduce the probability of generating biologically redundant names and more taxonomic confusion.